Using factor theorem, Show that (a – b) is the factor of a (b²- c²) +b (c²-a²) + c (a²-b²) Answer Plzzz

Question

Using factor theorem, Show that (a – b) is the factor of a (b²- c²) +b (c²-a²) + c (a²-b²) Answer Plzzz

in progress 0
Margaret 5 months 2022-01-06T01:23:29+00:00 1 Answer 0 views 0

Answers ( )

    0
    2022-01-06T01:24:58+00:00

    Answer:

    a(b²-c²)+b(c²-a²)+c(a²-b²)

    =ab²-ac²+bc²-a²b+a²c-b²c

    =ab²-a²b-ac²+bc²+a²c-b²c

    =ab(b-a)-c²(a-b)+c(a²-b²)

    =-ab(a-b)-c²(a-b)+c((a+b)(a-b))

    =(a-b)[-ab-c²+c(a+b)]

    =(a-b)[-ab+cb-c²+ac]

    =(a-b)[-b(c-a)-c(c-a)]

    =(a-b)(b-c)(c-a)

    Read more on Brainly.in – https://brainly.in/question/3804487#readmore

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )